Vascularized Pericranial Flap for Endonasal Anterior Skull Base Reconstruction - Giurintano, Jonathan; McDermott, Michael W.; El-Sayed, Ivan H. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction As the limits of advanced skull base malignancies that can be managed through an endoscopic endonasal approach continue to be expanded, the resultant anterior skull base defects are of increasing size and complexity. In the absence of nasoseptal or turbinate flaps, the vascularized pericranial flap has been employed at our institution with excellent results.Objective The study aimed to review the outcomes of patients who underwent endonasal anterior craniofacial resection with anterior skull base reconstruction using a vascularized pericranial flap.Design Retrospective chart review of patients treated by the University of California – San Francisco minimally invasive skull base service from the years 2011 to 2017. Average duration of follow-up was 16.4 months.Setting This study was conducted at Academic tertiary referral center.Participants A total of nine patients with advanced anterior cranial base malignancies were identified who were treated with a minimally invasive, endoscopic anterior craniofacial resection from the years 2011 to 2017. Due to the nature of the resection in these patients, nasoseptal flaps and inferior/middle turbinate flaps were unavailable or insufficient for anterior skull base defect repair. Each patient underwent reconstruction of the anterior cranial base defect using an anteriorly based pericranial flap harvested by bicoronal incision, and tunneled anteriorly to the nasal cavity through a frontoethmoidal incision.
Keywords: Anterior; skull base; reconstruction; pericranial; flap